Pocket settings for promoting on-campus social learning: FGD - Salih, Sarah Abdulakreem; Ismail, Sumarni; Azmi, Athira; Bajish, Ahmed Sadek (Human Resource Management Academic Research Society (HRMARS), 2023)
Abstract: Recently, the implementation of outdoor learning spaces has emerged as a crucial measure to enhance the academic experience by facilitating the augmentation of students' social interactions and learning endeavours. Investigating Asian universities reveals that these campuses mainly prioritise indoor traditional learning approaches while exhibiting littleintegration of social learning practices that align with academic objectives. Hence, it is vital to augment the social learning activities of students within the premises of university campuses in Asia, with the aim of enhancing the overall social learning experience. This study aims to identify the design attributes of pocket settings for enhancing social learning activity in Asian universities. This study utilised qualitative, semi-structured focus group discussions (FGDs) involving professionals and academicians in the field of architecture to assess the attributes of pocket settings on the Asian campus grounds. The data is analysed using ATLAS.ti.8. The findings indicate that the implementation of design attributes, such as design and layout, elements and activities, accessibility and proximity, and safety and security, is critically important for providing successful pocket settings on university grounds that greatly enhance the social learning experience. The results of this study make a valuable contribution to the development of a pocket setting model specifically designed for Asian campus environments. This model aims to effectively integrate informal spaces into social learning activities, ultimately enhancing the overall academic social learning experience.